The analysis of occupational satisfaction of resident physicians having emergency medicine education - Kaynak, Mahmut Firat; Altintop, Ismail; Cikriklar, Halil Ibrahim; Ozdemir, Fatma; Gafurogulları, Sibel; Koca, Nizameddin (The European Research Journal, 2016)
Objectives. The personnel of Emergency Service (ES) is under stress due to the intensity of the resulting from the very nature of the work to be performed in this department, which is characterized by the need of providing rapidly medical care to patients with often severe or even life-treating health problem and by though working conditions. In our study, we aimed to determine the satisfaction of resident physicians about choosing the emergency medicine, the factors affecting this satisfaction, and the plans of these resident doctors.Methods. In our study, we surveyed 66 resident physicians working in 4 emergency centres. The resident physicians completed the survey form given to them.Results. Regarding the occupational satisfaction of 66 resident physicians participating working in emergency medicine department, we obtained the following results: 54.5% (n=36) satisfied, 22.7% (n=15) not satisfied, 9.1% (n=6) more satisfied than expected, and 9.1% (n=6) neither satisfied nor not satisfied. When the opinions of residents were asked about how likely it was that they would be working in emergency medicine in 10 years hence, 40.9% (n=27) of the participants stated that they wanted to work there, 36.4% (n=24) stated that they were not sure, and 22.7% (n=15) stated that they didn’t want to work.Conclusions. The encouraging legal regulations in regard to physicians’ rights about working in emergency medicine branch should be revised, working conditions should be improved, and it is important to provide young doctors with carrier and educational opportunities. Otherwise, it is likely that we might lose our national and international achievements in emergency medicine branch.